Microtremor-Based Mitigation Pathways and Disaster Post Placement in the Merapi Geotourism Area, Yogyakarta - Kesya Lutfiany Fatihah; Maria Diyah Ayu Wulandari; Anwar Said Pintrandhita; Ryan Surya Dharma Tarigan (Yayasan Ghalih Pelopor Pendidikan, 2025)
Cangkringan District, located on the slopes of Mount Merapi, is highly susceptible to volcanic and seismic activity, posing risks to its residents and the thriving geotourism sector. This study aims to determine optimal mitigation pathways and disaster post placements using geophysical methods, specifically the HVSR microtremor method and GGMPlus satellite gravity data. The research analyzed seismic vulnerability, ground acceleration, and shear wave velocity (Vs30), combined with gravity anomaly data, to identify high-risk areas and safe zones. The results produced a detailed mitigation map, guiding the placement of two disaster posts and evacuation routes based on soil vulnerability, topography, and rock density. These findings contribute to disaster risk reduction efforts and sustainable geotourism development by enhancing evacuation efficiency and safety for residents and tourists. This integrated approach offers a model for disaster-prone regions, balancing economic growth with safety and resilience against geological hazards